PERBANDINGAN KEMAMPUAN BERPIKIR KRITIS ANTARA TPS DAN TTW DENGAN MEMPERHATIKAN MINAT BELAJAR - Ajeng Perwito Sari; Eddy Purnomo; Yon Rizal (FKIP Unila, 2015)
The study examines the comparative study of critical thinking skills between studentstaught using cooperative learning model of Think Pair Share and Think Talk Write toobserve students interest in social studies integrated semester of eighth grade students ofSMP Global Madani Bandar Lampung. The results of data analysis showed (1) there isa difference between the critical thinking skills of students whose learning usingcooperative learning model TPS and TTW, (2) critical thinking skills in students whohave a low interest in learning by using cooperative learning model of TPS is higherthan by using learning using cooperative models TTW, (3) critical thinking skills instudents who have a high interest in learning cooperative learning model TPS is lowerthan learning by using a model of cooperative TTW type, (4) there is an interactionbetween the model of cooperative learning with students interest in critical thinkingskills.Penelitian ini mengkaji tentang studi perbandingan kemampuan berpikir kritis antarasiswa yang diajar menggunakan model pembelajaran kooperatif tipe Think Pair Sharedan Think Talk Write dengan memperhatikan minat belajar siswa pada mata pelajaranIPS Terpadu siswa kelas VIII semester ganjil SMP Global Madani Bandar Lampung.Hasil analisis data menunjukan (1) ada perbedaan kemampuan berpikir kritis antarasiswa yang pembelajarannya menggunakan model pembelajaran kooperatif tipe TPSdan TTW, (2) kemampuan berpikir kritis pada siswa yang memiliki minat belajarrendah yang pembelajarannya menggunakan model kooperatif tipe TPS lebih tinggidibandingkan yang pembelajaannya menggunakan model kooperatif tipe TTW, (3)kemampuan berpikir kritis pada siswa yang memiliki minat belajar tinggi yangpembelajarannya menggunakan model kooperatif tipe TPS lebih rendah dibandingkanyang pembelajarannya menggunakan model koopratif tipe TTW, (4) ada interaksi antaramodel pembelajaran kooperatif dengan minat belajar siswa pada kemampuan berpikirkritis.Kata kunci : berpikir kritis, minat, TPS, TTW